Psychological effects of human-nature connection and the effectiveness of nature-based interventions on mental health in adults - Ma, Jingni (The University of Edinburgh, 2023)
Despite growing research on human-nature interaction, there remains a lack of understanding of the impact of physical engagement in nature and whether nature-based intervention is effective in improving mental wellbeing, mindfulness, sleep quality, and mood in adults. The aims of this thesis are to deepen our understanding of the psychological effects of human-nature interactions in relation to gardening and keeping houseplants, and to test the effectiveness and mechanisms of a targeted nature-based intervention on mental health outcomes. The thesis investigated the psychological effects of human-nature connection from home settings to the community and to wider public nature environments. Firstly, the psychological effects of houseplants care behaviour on health and wellbeing community gardening, and the experience of engaging in community gardening amongst Chinese adults in urban areas were examined. Next, there is an examination of the effectiveness of greenspace-based walking intervention on mental health – a systematic review was carried out, and then a randomised control study of nature-based mindful walking was conducted in the UK with the design based on the findings of the systematic review. A review of the literature on the impact of nature on mental health indicated that research on this topic has been done mostly in developed countries, especially in the Western world. A few studies regarding the human-nature connection in psychology have been investigated in China, which is now facing growing urbanisation, and environmental problems, and increasing levels of mental health concerns. A research gap has also been identified regarding the effectiveness of walking in nature (i.e., greenspace) on mental health in the UK, especially for university students’ mood disturbance and sleep difficulties during the COVID-19 pandemic. As many Chinese adults living in urban environments do not have ready access to outdoor gardens, the first empirical work was to investigate the impact of houseplants on mental health. Using a questionnaire-based survey, two empirical studies regarding the care of houseplants (n = 421) are reported. The first part of this research revealed that houseplants carers reported significantly higher levels of mental well-being and mindfulness compared with non houseplants carers. Additionally, taking care of houseplants was positively related to greater levels of mental wellbeing and mindfulness, and the Universalism value was found to significantly relate to various houseplants care behaviours. The second study highlights the importance of one’s attitude, perceived behaviour controls (i.e., self-efficacy), and intentions on behaviours around keeping houseplants. Moving to community settings from the house, a grounded theory study (n = 21) of Chinese community gardeners found participants perceived that community gardening activities benefited their physical health, mood, sense of connection with nature, communication, spirituality, and personal growth, but that Chinese gardeners believed they needed more support from the government to construct more gardens. This study bridges the gap of understanding Chinese city residents’ experiences of outdoor gardening activities with respect to health and wellbeing. These findings imply that positively interacting with nature through gardening and indoor houseplants leads to a better human-nature relationship and improved mental health outcomes for adults in urban China. The subsequent chapters (5–6) of the thesis present an evaluation of the effectiveness of greenspace-based walking interventions on mental health in the UK. A systematic review of the literature reviewed 17 studies to provide new insight on the effects of greenspace-based walking interventions through a narrative synthesis of existing evidence. The findings revealed that nature-based walking was associated with benefits such as positive mood, wellbeing, anxiety-reduction, rumination, and mindfulness. However, only four of the included experimental studies in the systematic review employed a randomised control design. To address this gap, a novel randomised control study was conducted, using a pre-test, intervention, post-test, and delayed post-test design, where participants (N = 104 UK university students) were allocated to nature or urban walking conditions. Self-reported online assessment questionnaires were used as an evaluation tool. Participants were randomly assigned to either a nature or an urban walking environment, and they followed a prescribed route involving walking for around 35 minutes daily for seven consecutive days with instructions on how to engage in the walk mindfully. The results revealed no difference between nature and urban walking conditions but indicated that outdoor mindful walking improved the participants’ mindfulness and sleep quality, and decreased mood disturbance. The improvement of sleep quality was linked to the relationship between the mindful walking intervention and the improvement of mood amongst university students, suggesting that mindful outdoor walking enhances mood through improving sleep. This thesis highlights the importance of human-nature connections, and the mental health benefits of engaging in various nature-based activities and interventions in China and the UK. It also addresses gaps in psychological research on ways to promote human-nature interaction through gardening and planting; and deepens our understanding of how nature-based walking interventions can enhance adults’ wellbeing, mood, mindfulness, and sleep quality. The findings of this thesis have implications for practice and policy and will impact public health (e.g., investment in community gardens for urban residents; encouraging people to grow indoor plants), and the impact on clinical practice of encouraging organisations (e.g., university mental health service) to deliver effective interventions to young adults with their sleep and mood problems.
The psychological effects of human-nature connection and the effectiveness of nature-based interventions on mental health in adults
Keywords: psychological effects of gardening; nature walking effectiveness; human-nature relationship; urban China; community gardening for mental health; sleep difficulties; COVID-19